2015
DOI: 10.1016/j.athoracsur.2015.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric End-Stage Failing Hearts Demonstrate Increased Cardiac Stem Cells

Abstract: Background We sought to determine the location, expression, and characterization of cardiac stem cells (CSCs) in children with end-stage heart failure (ESHF). We hypothesized ESHF myocardium would contain an increased number of CSCs relative to age-matched healthy myocardium, and ESHF-derived CSCs would have diminished functional capacity as evidenced by reduced telomere length. Methods Tissue samples were obtained from the explanted hearts of children undergoing heart transplantation with ESHF, defined as N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…The results of the present study also demonstrated that c-kit and nanog were correlated with the degree of ventricular remodelling, which demonstrated that neutrophils are able to secrete a large number of inflammatory cells (27), and inhibit the expression of c-kit and nanog during early inflammation (28,29). In the present study, this pathological process was verified from the molecular and genetic level.…”
Section: Discussionsupporting
confidence: 71%
“…The results of the present study also demonstrated that c-kit and nanog were correlated with the degree of ventricular remodelling, which demonstrated that neutrophils are able to secrete a large number of inflammatory cells (27), and inhibit the expression of c-kit and nanog during early inflammation (28,29). In the present study, this pathological process was verified from the molecular and genetic level.…”
Section: Discussionsupporting
confidence: 71%
“…As reported by Amir et al, these cells coexpress cardiac (SERCA) and stem cell markers and have the ability to differentiate into cardiomyocytes (16). Although there is an age-dependent decline in the relative density of these cells in hearts with normal cardiac function, work by Wehman et al (19) showed an increase in cardiac stem cell numbers in end-stage pediatric HF patients when compared with congenital heart disease controls with normal cardiac function. The number of cardiac stem cells did not decline with age in children with HF, in contrast with the decline seen in age-matched controls without HF.…”
Section: Discussionmentioning
confidence: 83%
“…Neonatal and adult c-kit + /CD45 − CPCs, nCPCs and aCPCs respectively, were isolated from RAA biopsies using our previously described protocol involving explant plating, immune-bead selection, and expansion. 26, 2831 All tissue specimens, even those weighing between 20 to 40 mg, generated c-kit + CPCs, which were successfully grown beyond 30 days and, on average, yielded greater than 18×10 6 cells. At passage 3 (P3), nCPCs and aCPCs had similar cellular morphologies and were negative for expression of hematopoietic markers (CD34 and CD45), endothelial markers (CD31; PECAM-1), mast cell markers (tryptase), certain cardiomyocyte lineage-specific transcription factors (GATA4 and ISL1), and embryonic stem cell markers (SSEA3 and SSEA4).…”
Section: Resultsmentioning
confidence: 99%